Cost Consciousness Among Dermatologists - AlFada MA (Clinical, Cosmetic and Investigational Dermatology)
Mohammed A AlFada Department of Dermatology, College of Medicine, King Saud University, Riyadh, Saudi ArabiaCorrespondence: Mohammed A AlFada, Dermatology Department, College of Medicine, King Saud University, PO Box 240997, Riyadh, 11322, Saudi Arabia, Email malshahwan@ksu.edu.saBackground: Physicians are responsible for most decisions related to resource allocation and healthcare expenditures, and should consider cost in their decision-making approach.Objective: To measure cost consciousness among dermatologists, evaluate their understanding of cost-related concepts, and explore what prevents them from factoring cost into their daily practice decisions.Methods: This cross-sectional survey-based study involved dermatologists from different practice types and work environments. The survey is split into four sections, focusing on participants’ (1) demographic and workplace information; (2) knowledge of cost-related terms; (3) personal cost-consciousness level; and (4) perceived barriers to factoring cost into clinical decisions.Results: Overall, 132 practicing dermatologists participated in the survey. Approximately 82% of them had heard of cost-effectiveness, but only 10% really understood how to indicate, interpret, and calculate it, while most had never heard of cost-consciousness or cost-containment. The majority agreed that it is the responsibility of physicians to contain medication costs, and almost all agreed that physicians need to do more to limit the prescription of unnecessary medications. Sex, long work experience, mixed administrative and clinical roles, and working in a mixed practice setting were all associated with cost consciousness. Multivariate regression analysis showed a significant association between having a mixed clinical and administrative professional role and cost consciousness.Conclusion: Although most dermatologists agree that it is the responsibility of physicians to contain the cost when deciding on medication, they have limited understanding of cost-related concepts. Having a mixed clinical and administrative roles was a significant predictor of cost conscious behavior.Keywords: cost, cost consciousness, cost effectiveness, cost containment and dermatology